Kadar Hormon Pertumbuhan Sapi Bali Lebih Rendah di Nusa Penida Daripada Daerah Bali Lainnya(LEVELS OF GROWTH HORMONE BALI CATTLE IN NUSA PENIDA LOWER THAN OTHER BALI REGIONS) - Suwiti, Ni Ketut; Tenaya, I Wayan Masa; Besung, I Nengah Kerta (Jurnal Veteriner; Vol 18 No 2 (2017)DO - 10.19087/jveteriner.2017.18.2.226, 2017)
The objective of this research was to compare the levels of growth hormone in bali cattle reared in the purification of Nusa Penida with those from other regions in Bali Province. A total of 320 sera samples were collected from bali cattle reared in Nusa Penida, Klungkung, Tabanan, Buleleng and Bangli. The levels of growth hormone was determined by using sandwich Enzime Linked Immunosorbent Assay (ELISA). The results showed that a diverse levels of growth hormone in Bali cattle were observed in Bali cattle. The lowest growth hormone levels (576.4 pg/mL) was found in Bali cattle reared in Nusa Penida and the highest levels (5044.08 pg/mL) were found in the Buleleng regency. It was concluded that bovine growth hormone levels varies, depending on the regions of rared of Bali cattle. ABSTRAK Penelitian ini bertujuan untuk mendeteksi kadar hormon pertumbuhan sapi bali yang dipelihara di wilayah pemurnian Nusa Penida dan wilayah lainnya di Provinsi Bali. Sebanyak 320 sampel serum sapi bali betina dewasa dikumpulkan dari peternakan rakyat di Nusa Penida Klungkung, Tabanan, Buleleng, dan Kabupaten Bangli. Kadar hormon pertumbuhan dideteksi dengan metode Enzime Linked Immunosorbent Assay (ELISA). Hasil penelitian menunjukkan, kadar hormon pertumbuhan sapi bali terendah (576,4 pg/mL) ditemukan pada sapi bali yang dipelihara di Nusa Penida, sedangkan kadar hormon tertinggi (5044,08 pg/mL) ditemukan pada sapi bali yang dipelihara di Kabupaten Buleleng. Disimpulkan bahwa kadar hormon pertumbuhan sapi bali berbeda-beda, tergantung wilayah tempat pemeliharaan sapi bali.